Magnetic behavior of the novel pentagonal-bipyramidal erbium(III) complex (Et3NH)[Er(H2DAPS)Cl2]: high-frequency EPR study and crystal-field analysis - Spillecke, Lena; Koo, Changhyun; Maximova, Olga; Mironov, Vladimir S.; Kopotkov, Vycheslav A.; Korchagin, Denis V.; Vasiliev, Alexander N.; Yagubskii, Eduard B.; Klingeler, Rüdiger (Dalton transactions, 2021)
We report the synthesis, crystal structure and magnetic properties of the new heptacoordinated mononuclear erbium(III) complex (Et3NH)[Er(H2DAPS)Cl2] (H4DAPS = 2,6-diacetylpyridine bis-(salicylhydrazone)) (1). The coordination polyhedron around the Er(III) ion features a slightly distorted pentagonal bipyramid formed by the pentagonal N3O2 chelate ring of the H2DAPS ligand in the equatorial plane and two apical chloride ligands. Detailed high-frequency/high-field electron paramagnetic resonance (HF-EPR) studies of 1 result in the precise determination of the crystal field (CF) splitting energies (0, 290 and 460 GHz) and effective g-values of the three lowest Kramers doublets (KDs) of the Er(III) ion. The obtained HF-EPR data are in good agreement with the results from CF analysis for the Er(III) ion based on the simulation of the dc magnetic data of 1. The results from dynamic susceptibility measurements indicate that there is no slow relaxation of magnetisation behaviour. This observation is discussed in terms of the electronic structure of 1 obtained from experimental and theoretical results.
Im Titel sind die Zahlen "3" und "2" tiefgestellt
Gesehen am 18.07.2022